Proposed Marketing Strategy for Truck Coffee Shop in Bandung (Study Case: Ideologi Kopi) (The Indonesian Journal of Business Administration, 2021)
Truck Coffee Shop business is one of the business that nowadays have a lot of interest, which can be seen with many truck coffee shops that have recently appeared. The huge number of coffee lovers and lifestyle also supported this phenomenon for people who love to hang out after activities with friends or colleagues. One of the players in the coffee shop business is Ideologi Kopi. In order to become a truck coffee shop, the owner uses his own VW cart. Ideologi Kopi creates a comfy retro atmosphere as a truck coffee shop with a comfortable retro concept that makes customers feel like their own car in the mall side area. Until recently, the majority of loyal customers of Ideologi Kopi are from the relation of the owner knowledge. Ideologi Kopi must increase their market share with the large number of competitors in this industry and get new loyal customers to sustain the business for a long time. Author is using elements from marketing strategy to identify some of the necessary factor and it was discovered on the basis of external analysis that this industry has intense competition. Competitor comes mainly from truck coffee shop, who normally just a conventional coffee shops, because they wanted to follow for a trend. In addition, from an internal point of view, Ideologi Kopi also mostly relies only on Instagram without another promotional program. Ideologi Kopi has several limited installation problems with the use of its own VW cart. SWOT analysis was then obtained from internal and external analysis of factors in Ideologi Kopi. If Ideologi Kopi is not yet optimal for looking for new customers and retaining it, then it can be found from SWOT analysis. Several important matters have also been found from competitor and customer analysis that feel important and can be further enhanced by Ideologi Kopi. The author also suggested several elements of alternative marketing strategies from the matrix TOWS analysis; Segmentation, Targeting, and Positioning (STP) for the business, including within are Points of Parity (PoP), Points of Difference (PoD) to know its value in terms of Value Proposition alongside proposed Marketing Mix with a 7P’s also a support operation strategy, hoping that Ideologi Kopi can implement. These alternatives enhance promotion by representing several strong points on Ideologi Kopi and social media ad placement, collaborating with social media influencers, developing loyalty program and product promotion, and improving Ideologi Kopi facilities.Keywords: Truck Coffee Shop, Alternative Solutions, Marketing Strategy, Promotion, SWOT analysis